Adoption Pattern of Solar Cooker in different Agro- ecological Situations of District Ropar (Punjab) (Indian Journal of Extension Education, 2015)
Sustainable development requires an organized efforts to develop and defuse new technology appropriate for agricultural production system, renewable energy systems and pollution controls. Energy is one of the vital resources for development and survival of mankind. We are fortunate to have abundant sunlight during most part of the year. This untapped renewable energy could be the best substitute to save conventional fuels used for domestic cooking and at the same time keep the environment clean. The solar cookers if available can offer a partial solution to multitude of cooking problems faced by people of low income. A properly designed and improved cooker if introduced in the market in mass scale can supplement the cooking energy requirement of several millions of people and reduce deforestation and environmental problems associated with the use of fossil fuels. Solar cooker which is safe and simple to operate can satisfactorily be used for cooking in the presence of sunshine. The present study has been designed with the objective know the fuel management practices adopted by women in rural areas of three agro-ecological situations of Punjab. The results showed that the usage varies with the topographical situation. In sub-mountainous area, the usage of electricity and LPG is 24per cent and 48per cent respectively whereas the usage of firewood is maximum (88per cent). On the other hand, in the plain area, the usage of electricity and LPG is 48per cent and 96per cent respectively and that of firewood is 40 per cent only. Electricity which is used by 40per cent households is considered dangerous, expensive and irregular in supply due to frequent power failure. LPG, which is used by 80per cent households, is also considered as dangerous, having high initial investment and limited in supply. Problem reported with the use of kerosene, which is used by 33.33 per cent households includes unpleasant odour, limited supply and adulteration. In case of non- commercial. Firewood which is used by 63.33per cent households with maximum usage in the sub- mountainous area , where it is used by 88per cent households is considered as unclean, giving smoke, creating health problems, laborious to collect, difficult to procure and difficult to store. Average saving on fuel per year by the rural households after adopting solar cooker is calculated as a gross reduction of ` 1740 per year and a net saving of 33.33 per cent.